Through the Wall - Moffett, Cleveland, 1863-1926 (Salt Lake City, UT : Project Gutenberg, 2004)
"Through the Wall" by Cleveland Moffett is a novel written in the early 20th century. The story centers around Paul Coquenil, a renowned French detective who finds himself embroiled in a complex and dangerous criminal case after an inexplicable encounter with a mysterious candle seller in Notre-Dame. This encounter awakens his instincts and thrusts him into a web of intrigue involving love, suspicion, and a plot that could threaten his life and career. The opening of the book sets the stage for Coquenil's internal struggle, showcasing his faith in intuition and uncanny knowledge that often guide his investigations. As he walks through Paris, reflecting on his past as a celebrated detective now facing personal turmoil, he encounters a distressed girl who unknowingly shares a dream that is deeply interconnected with his own history. This moment propels him into a series of unforeseen events, including his upcoming appointment in Brazil, a sudden murder, and a romantic tension with Alice, the candle seller. Meanwhile, Alice grapples with her feelings for Lloyd Kittredge, an American, whose life becomes entangled with Coquenil$1 (Bs investigation as he is accused of murder. The opening chapters create an atmosphere filled with suspense and foreshadow the twists that await. (This is an automatically generated summary.)s
Release date is 2004-02-01
Produced by Suzanne Shell and PG Distributed Proofreaders
Keywords: Detective and mystery stories